The violence triangle in Khaled Hosseini’s A thousand splendid suns - Wshyar, Mustafa (AMERICANA E-journal of American Studies in Hungary, 2018)
This paper aims to explore Johan Galtung’s theory of the violence triangle through Khaled Hosseini’s novel A Thousand Splendid Suns. I will focus on how direct violence is represented as a result of structural and cultural violence. Moreover, I will also analyze the role of the invisible violence in promoting the visible violence, which is bordering on direct violence. I will argue that direct violence documents the rest of the types since that is the only visible aggression one that can be seen and witnessed through the threshold of the quasi-visible world of the novel.